TEACHING WRITING USING GOOGLE CLASSROOM PLATFORM FOR VOCATIONAL HIGH SCHOOL STUDENTS - Sianipar, Davit Eben Ezer; Gultom, Miranda Timor Leste (Transpublika Publisher, 2022)
The objective of this research is to prevend the usefulness of the Google Classroom platform in the teaching writing for students of vocational level. The type of the research that researchers used in this research was experimental research. The subjects in this research were the students of XI TI in SMK Parbina Nusantara, Pematangsiantar. This class consists of 37 students. To collect the data, researchers conducted pre-test and post-test. The pre-test was carried out in the learning process before the researchers applied the Google Classroom, while in the implementation of the post-test, the researchers applied the use of Google Classroom first, then evaluated students’ writing skills. Based on the discovery results in this research, researchers found that Google Classroom is a useful media in teaching writing for vocational high school students.